Performance Audit of Functioning of Anganwadi Centres in Rajasthan (2015-2018) - CAG of India (CAG of India)
Anganwadi Centres are the first outpost for delivery of supplementary nutrition, pre-school education and other services under the Integrated Child Development Services (ICDS) programme to children in the age group of 6 months to 6 years, pregnant women and lactating mothers. The objective of the thematic audit was inter alia to assess regular and effective delivery of services by AWCs. Some of the significant audit findings include deficiencies in planning, availability of infrastructure, equipment and manpower and lack of regular supervision. There was shortfall of 35.24 per cent and 41.32 per cent in coverage of targeted eligible beneficiaries for supplementary nutrition and pre-school education respectively. A substantial number (23.30 lakhs) of malnourished children were deprived of additional nutrition. None of the AWCs were able to provide micronutrient fortified supplementary nutrition as the Self Help Groups who supplied food did not have the capacity for fortification. Shortage of critical personnel like CDPOs/ACDPOs (52.47 per cent) and Supervisors (31.68 per cent) and shortage in prescribed trainings also affected various aspects of delivery of the programme. These deficiencies coupled with lack of regular supervision resulted in weaknesses in the delivery of services.
For the Period 2015-16 to 2017-18